2004
DOI: 10.1158/1078-0432.ccr-04-0245
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Tumor Cells in Bone Marrow Three Years after Diagnosis in Disease-Free Breast Cancer Patients Predict Unfavorable Clinical Outcome1

Abstract: Purpose: The aim of the study was to explore the value of analyzing bone marrow (BM) for the presence of isolated tumor cell(s) (ITCs) in disease-free breast cancer patients 3 years after diagnosis.Experimental Design: ITCs in BM at operation was found to be an independent prognostic factor in 817 breast cancer patients. Among these, 356 disease-free patients were analyzed with a second BM after 3 years follow-up (median 40 months, SD 3 months, range 29 -52). ITC was detected by immunocytochemistry with anticy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
113
2
14

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(138 citation statements)
references
References 21 publications
9
113
2
14
Order By: Relevance
“…26 Repeated bone marrow aspiration performed under local anesthesia also can be performed to obtain information regarding the persistence of DTCs. [18][19][20][21] Bone marrow aspirate is then transferred into heparinized tubes. 10,[13][14][15]18,23,24,27 Ethylenediamine tetraacetic acid 24 or sodium citrate 28 also may be used as anticoagulant.…”
Section: Methodological Aspects Of Bone Marrow Processing Collection mentioning
confidence: 99%
See 3 more Smart Citations
“…26 Repeated bone marrow aspiration performed under local anesthesia also can be performed to obtain information regarding the persistence of DTCs. [18][19][20][21] Bone marrow aspirate is then transferred into heparinized tubes. 10,[13][14][15]18,23,24,27 Ethylenediamine tetraacetic acid 24 or sodium citrate 28 also may be used as anticoagulant.…”
Section: Methodological Aspects Of Bone Marrow Processing Collection mentioning
confidence: 99%
“…8,10,13,14,19,25,28,30 Negative immunomagnetic separation of epithelial tumor cells has been investigated in a single, large clinical trial but showed no significant advantage over Ficoll density-gradient centrifugation. 8 For this reason and because of the significantly higher costs of immunomagnetic separation, the immunomagnetic separation procedure is not recommended currently for routine use.…”
Section: Processing Of Bone Marrow Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that investigated the prognostic value of CTCs/DTCs at the time of completion of adjuvant therapy [42, 106,107] showed that the detection of DTCs [42,108] and CTCs [106] after the completion of chemotherapy is associated with an unfavorable clinical outcome [103,105]; further reviewed by Ignatiadis et al [109]. In keeping with this work suggesting diagnostic and prognostic relevance for CK19, more recently full-length CK19 has been detected in bone marrow specimens from breast cancer patients and is associated with the presence of overt metastases and poor survival rates [110].…”
Section: Cytokeratin 19mentioning
confidence: 99%